Inhibition of Arginase 1 Liberates Potent T Cell Immunostimulatory Activity of Human Neutrophil Granulocytes - Vonwirth, Verena; Bülbül, Yagmur; Werner, Anke; Echchannaoui, Hakim; Windschmitt, Johannes; Habermeier, Alice; Ioannidis, Sonia; Shin, Niu; Conradi, Roland; Bros, Matthias; Tenzer, Stefan; Theobald, Matthias; et al. (Frontiers in Immunology, 2021)
Myeloid cell arginase-mediated arginine depletion with consecutive inhibition of T cell functions is a key component of tumor immune escape. Both, granulocytic myeloid-derived suppressor cells. (G‑MDSC) and conventional mature human polymorphonuclear neutrophil granulocytes (PMN) express high levels of arginase 1 and can act as suppressor cells of adaptive anti-cancer immunity. Here we demonstrate that pharmacological inhibition of PMN-derived arginase 1 not only prevents the suppression of T cell functions but rather leads to a strong hyperactivation of T cells. Human PMN were incubated in cell culture medium in the absence or presence of an arginase inhibitor. T cells from healthy donors were then activated either polyclonally or in an antigen-specific manner in the supernatants of the PMN cultures at different PMN-T cell ratios. T cell proliferation was completely suppressed in these supernatants in the absence of an arginase inhibitor. Arginase inhibition led to a strong hyperinduction of T cell proliferation, which exceeded control activation conditions up to 25-fold. The hyperinduction was correlated with higher PMN-T cell ratios and was only apparent when PMN arginase activity was blocked sufficiently. The T cell stimulatory factor was liberated very early by PMN and was present in the < 3 kDa fraction of the PMN supernatants. Increased T cell production of specific proinflammatory cytokines by PMN supernatant in the presence of arginase inhibitor was apparent. Upon arginase inhibition, downregulation of important T cell membrane activation and costimulation proteins was completely prevented or de novo induction accelerated. Antigen-specific T cell cytotoxicity against tumor cells was enhanced by PMN supernatant itself and could be further increased by PMN arginase blockade. Finally, we analyzed anergic T cells from multiple myeloma patients and noticed a complete reversal of anergy and the induction of strong proliferation upon T cell activation in PMN supernatants by arginase inhibition. In summary, we discovered a potent PMN-mediated hyperactivation of human T cells, which is apparent only when PMN arginase-mediated arginine depletion is concurrently inhibited. Our findings are clearly relevant for the analysis and prevention of human tumor immune escape in conjunction with the application of arginase inhibitors already being developed clinically.